Hereditary motor and autonomic neuronopathy 1 maps to chromosome 20q13.2-13.3 - W. Marques Jr.; M.B. Davis; P.M. Abou-Sleiman; V.D. Marques; W.A. Silva Jr.; M.A. Zago; C.S. Sobreira; A.A. Barreira (Brazilian Journal of Medical and Biological Research, 2004)
The spinal muscular atrophies (SMA) or hereditary motor neuronopathies result from the continuous degeneration and death of spinal cord lower motor neurons, leading to progressive muscular weakness and atrophy. We describe a large Brazilian family exhibiting an extremely rare, late-onset, dominant, proximal, and progressive SMA accompanied by very unusual manifestations, such as an abnormal sweating pattern, and gastrointestinal and sexual dysfunctions, suggesting concomitant involvement of the autonomic nervous system. We propose a new disease category for this disorder, `hereditary motor and autonomic neuronopathy', and attribute the term, `survival of motor and autonomic neurons 1' (SMAN1) to the respective locus that was mapped to a 14.5 cM region on chromosome 20q13.2-13.3 by genetic linkage analysis and haplotype studies using microsatellite polymorphic markers. This locus lies between markers D20S120 and D20S173 showing a maximum LOD score of 4.6 at D20S171, defining a region with 33 known genes, including several potential candidates. Identifying the SMAN1 gene should not only improve our understanding of the molecular mechanisms underlying lower motor neuron diseases but also help to clarify the relationship between motor and autonomic neurons.